Agroforestry adoption and its influence on soil quality under smallholder maize production systems in western Kenya - Henry Tamba Nyuma; Ruth Njoroge; Abigael Nekesa Otinga (PLoS ONE, 2025)
Agroforestry, a sustainable land use practice, was introduced in western Kenya in the early 1990s as a soil fertility replenishment strategy. Since then, the effect of the practice on soil quality has seldom been evidenced. A study was conducted to assess the impact of agroforestry adoption on soil quality under smallholder maize systems in the region. Soil samples were collected from two land use practices: agroforestry adoption (90) and non-agroforestry adoption (30) at 0–30 cm depth from two locations (Busia and Kakamega counties). Results showed variations in soil characteristics between the study locations. Soils in Kakamega contained higher concentrations of soil organic carbon (SOC), exchangeable cations, and micronutrients. On average, agroforestry adoption significantly (P ≤ 0.05) improved soil physicochemical properties. Under agroforestry adoption, bulk density (BD) reduced by 21% (from 1.4 to1.1 g cm -3 ), while (SOC) increased by 75% (0.8–1.4%), P by 80% (3.0–5.4 mg kg -1 ), exchangeable K by 256% (0.3–8.0 cmol kg -1 ), Ca by 100% (1.0–2.0 cmol kg -1 ), S by 50% (0.2–0.3 mg kg -1 ), and Cu by 18% (2.8–3.3 mg kg -1 ). Agroforestry adoption significantly increased K and Cu levels above the critical thresholds of 0.4 cmol kg -1 and 1.0 mg kg -1 , respectively, at both locations. Sesbania sesban and Leucaena leucocephala influenced soil BD, pH and P (4.3.-7.0 mg kg -1 ), exchangeable K (0.4–0.7 cmol kg -1 ), Mg (0.1–0.2 cmol kg -1 ), and Mn (13.5–25.2 mg kg -1 ) at both locations, while Calliandra calothyrsus significantly increased SOC in Kakamega only. These findings highlight the significance of agroforestry in soil fertility management. Furthermore, Sesbania proved to be effective in enhancing the characteristics of soils at both sites, hence, the need for its inclusion in agroforestry extension messages. Further studies are needed to understand nutrient release mechanisms from agroforestry biomass and their influence on soil characteristics and maize yield in smallholder farming systems.